Helminth-induced IL-4 expands bystander memory CD8+ T cells for early control of viral infection. Issue 1 (December 2018) - Rolot, Marion; Dougall, Annette; Chetty, Alisha; Javaux, Justine; Chen, Ting; Xiao, Xue; Machiels, Bénédicte; Selkirk, Murray; Maizels, Rick; Hokke, Cornelis; Denis, Olivier; Brombacher, Frank; et al.
Abstract Infection with parasitic helminths can imprint the immune system to modulate bystander inflammatory processes. Bystander or virtual memory CD8+ T cells (TVM ) are non-conventional T cells displaying memory properties that can be generated through responsiveness to interleukin (IL)-4. However, it is not clear if helminth-induced type 2 immunity functionally affects the TVM compartment. Here, we show that helminths expand CD44hi CD62Lhi CXCR3hi CD49dlo TVM cells through direct IL-4 signaling in CD8+ T cells. Importantly, helminth-mediated conditioning of TVM cells provided enhanced control of acute respiratory infection with the murid gammaherpesvirus 4 (MuHV-4). This enhanced control of MuHV-4 infection could further be explained by an increase in antigen-specific CD8+ T cell effector responses in the lung and was directly dependent on IL-4 signaling. These results demonstrate that IL-4 during helminth infection can non-specifically condition CD8+ T cells, leading to a subsequently raised antigen-specific CD8+ T cell activation that enhances control of viral infection. Parasitic helminth infection is known to impact upon the host response to other bystander inflammatory processes. Here the authors show that IL4 production induced by helminth infection results in expansion of bystander CD8+ memory T cells and enhanced control to viral infection.